Simultaneous Detection of Bovine Rotavirus, Bovine Parvovirus, and Bovine Viral Diarrhea Virus Using a Gold Nanoparticle-Assisted PCR Assay With a Dual-Priming Oligonucleotide System - Wang, Mengmeng; Yan, Yue; Wang, Ruichong; Wang, Li; Zhou, Han; Li, Yijing; Tang, Lijie; Xu, Yigang; Jiang, Yanping; Cui, Wen; Qiao, Xinyuan (Frontiers in Microbiology, 2019)
Bovine rotavirus (BRV), Bovine parvovirus (BPV) and Bovine viral diarrhea virus (BVDV) are the pathogens that cause diarrhea primarily in newborn calves. A mixed infection of BRV, BPV, and BVDV makes clinical diagnosis difficult. In this study, we designed dual-priming oligonucleotide (DPO) primers the VP6 gene of BRV, VP2 gene of BPV, and 5'UTR gene of BVDV and synthesized gold nanoparticles (GNPs) with an average diameter of 10 nm. We combined the DPOs with the GNPs to develop a DPO-nanoPCR assay for detecting BRV, BPV, and BVDV. The annealing temperature, primer concentration, and GNP concentration were optimized for this assay. Compared to a conventional PCR assay, the DPO-nanoPCR assay allowed the use of a wider range of annealing temperatures (41-65℃) to effectively amplify target genes. PCR amplification was the most efficient at 56.2℃ using conventional primers. The optimal volume of all the primers (10 μM) was 1.0 μL. The optimal volume of GNPs (10 nM) for all the reactions was 0.5 μL. The detection limits of DPO-nanoPCR for pMD19-T-VP6, pMD19-T-VP2, and pMD19-T-5’UTR were 9.40×102copies/μL, 5.14×103copies/μL and 4.09×101copies/μL, respectively; and those using conventional PCR were 9.40×104copies/μL, 5.14×105copies/μL, and 4.09×104copies/μL, respectively. The sensitivity of DPO-nanoPCR was at least 100-fold higher than that of conventional PCR. The specificity detection showed that the DPO-nanoPCR was able to specifically detect BRV, BPV, and BVDV. Use of clinical samples indicated that target viruses can be detected accurately. Thus, DPO-nanoPCR is a new powerful, simple, specific, and sensitive tool for detecting mixed infections of BRV, BPV, and BVDV.